Efeitos da acupuntura e da eletroacupuntura sobre o estresse oxidativo e a inflamação decorrentes da torção/distorção do testículo em ratos - Acioli, Porfírio Cezar Passos (2014)
The efects of acupuncture (Ac) and Electroacupuncture (EAc) were evaluated using an experimental rat model of ischemia/reperfusion (IR) of the testis. In Traditonal Chinese Medicine, these forms of therapies are used in the promotion of organic equilbrium, through stimulation of specifc neurotransmiters producing nerve pathways, resulting in a analgesic and anti-nflammatory autonomic regulatory. response. In the study, 30 male Wistar rats, 279.6g average weight (230-30 g) were randomly divided into five groups. Al rats received intraperitoneal anesthesia (Ketamine 10 90mgKgXilazina mgKg), at the begining of the experiment, before the detorsion and at the end of the experiment. G1 group was submited to torsion of the testicle (TT), two complete turns (720º) with immediate detorsion (sham). The other groups (G2IR, G3Ac, G4EAc2 and G5EAc10) were submited to TT during 3 hours, folowed by detorsion and reperfusion during 4 hours. Five minutes before the detorsion Ac (G3Ac) or EAc (G4EAc2, G5EAc10) was aplied, under anesthesia, for 5 minutes. Next the testis was detorsioned and reperfused for 4 hours. At the end blod samples the right testicle were colected. Evaluated parameters included determination of reduced Glutathione (GSH), Malonaldehyde (MDA), Myeloperoxidase (MPO) and histopathology of the testicle. EAc (2 and 10 Hz) promoted signifcant increase in concentrations of GSH in plasma and in the rat estis of G4-G5, compared to the control G1. Ac did not alter signifcantly the concentrations of GSH in the G3 group compared to the G1. There was signifcant increase of MDA in tisue in groups G4-G5 and plasma MDA in al groups, compared to the G1. EAc (2 Hz and 10 Hz) signifcantly decreased the activity of MPO in the testis of rats subjected to TT (G4-G5), compared to the control G1. No signifcant diferences were observed in the activity of MPO comparing groups G4-G5 to group G1. It is concluded that EAc stimulation (2 and 10 Hz) atenuates oxidative stres and inflammatory response in rats subjected to testicular torsion/detorsion.